UTILIZATION OF SCIENCE LEARNING VIDEOS THROUGH THE PROBLEM BASED LEARNING (PBL) MODEL IN CRITICAL THINKING SKILLS OF GRADE V STUDENTS OF STATE ELEMENTARY SCHOOL 7 LINGE BANDA ACEH - Rosnawati, Siti; Sari, Siti Mayang; Kasmini, Lili (Jurnal Dikdas Bantara, 2024)
Problem Based Learning (PBL) has been identified as an effective learning model in integrating theoretical and practical learning through a student-centered approach. This study aims to determine the benefits of science learning videos through problem-based learning models to improve students' critical thinking skills. using descriptive qualitative research methods can explain in depth about the understanding of the use of learning videos through the PBL model. The results of the study showed that science learning videos shown by teachers through the PBL model improved students' critical thinking skills. It was proven that when the teacher asked about the learning videos shown, students were very enthusiastic about asking and giving positive responses and the teacher welcomed the students' responses well and provided supplies to see the improvement in students' critical thinking skills with assignments done at home. This study revealed based on the results of interviews with the principal and teachers that students were interested in learning using videos used by teachers as a learning tool, especially in science material and students responded very well with various constructive and critical questions.